Terroir - Ahluwalia, Monish; AlShenaiber, Leena; Balint, Liz; Barker, Bronwyn; Bider, Pascale; Bolger, Rachel; Chou, Sommer; Coles, Victoria; Conant, Amory; Coppens, Jarod; Craughwell, Meghan; Daniel, Tanya; et al. (Integrated Science Program, 2017)
Working in small groups, students in ISCI 3A12 examine the science behind wine making, from the art of viticulture to its eventual consumption by the public. Students perform literature-based reviews and original research in order to understand the wine industry and its complexity; including the environmental requirements and consequences of winemaking, the short- and long-term health effects of drinking wine, and what factors contribute to the quality, aroma, and taste of wine. This research was formatted to resemble a publicly accessible scientific article, and compiled to create each Vintage of Terroir.
Terroir Vintage 2017
Keywords: terroir; wine; science